Performance of Valencia sweet orange grafted onto dwarfing citrandarins - Devite, Fernando Trevizan; Bastianel, Marinês; Cristofani-Yaly, Mariângela; de Souza, Ana Júlia Borim; Gadanhoto, Biana Pelissari; Costa Arantes, Ana Carolina; De Azevedo, Fernando Alves (Frontiers in Plant Science, 2025)
Rootstock diversification is increasingly desired and necessary for the sustainability of citriculture, which is subject to adversity, such as the occurrence of Huanglongbing (HLB), which has impacted activity in most producing regions of the world. The objective was to evaluate the productivity, water-use efficiency, vegetative growth, and HLB incidence of Valencia sweet orange grafted onto three citrandarins (dwarfing) and Swingle citrumelo (standard). The field experiment was conducted under a high-density planting spacing of 5.0 m × 1.5 m (1333 plants ha−1) for citrandarin rootstocks (IAC 1600, IAC 1697, and IAC 1711) and a conventional spacing of 6.8 m × 2.5 m (588 plants ha−1) for Swingle citrumelo. The Swingle citrumelo rootstock combination with Valencia orange exhibited a larger canopy volume and higher per-plant yield, demonstrating high productivity under conditions of adequate water availability and conventional spacing. However, this combination also demonstrated lower water-use efficiency and higher susceptibility to HLB, particularly in 2024, highlighting its limitations for use in HLB-endemic regions. In contrast, combinations with citrandarins, especially IAC 1600, showed greater water-use efficiency, smaller canopy volume, and increased drought tolerance in higher-density planting. These combinations were also less susceptible to HLB and performed well in high-density planting systems, promoting the productive efficiency (kg fruit m3 canopy). The Swingle combination is recommended to maximize production in areas with abundant water resources and low HLB pressure, while citrandarin combinations, particularly IAC 1600, are better suited for regions with limited water availability and high HLB incidence.